Health Literacy of Diabetic Patients and its Impact on Disease Outcome - Abdul-Hasan, Ahmed A.; Yassin, Batool A. Gh. (Journal of the Faculty of Medicine Baghdad, 2018)
Background: Diabetes is one of the common and costly chronic health issues and a major cause of morbidity and mortality among other non-communicable diseases. Diabetes patients’ literacy about their diseases is to be addressed as an active factor of the disease outcome.Objectives: The objectives of the current study were to determine the overall health literacy level among diabetic patients attending the PHC centers and to test the association between the measured health literacy and their glycemic control.Methods: A cross-sectional study was conducted on a sample of randomly selected diabetic patients attending primary health care centers in Baghdad during the period from 15th July 2016 to 15th April 2017. Relevant demographic data were recorded and a specially designed tool was used to measure health literacy among diabetic patients, it consists of 15 question covering all aspects of health literacy (Scores 1 to 5 each question). The presence of diabetic complications were recorded and glycemic control of patients was documented by HbA1c.Results: With a total literacy score ranging from 15-75, the mean score of the patients in the current study was (mean = 43.34 ± 11.1 SD), and their recent HBA1c found to be ranging from 6.4 to 13.4 (mean = 10.25 ± 1 SD). A statistically significant association was found between patient literacy score and glycemic control (P